166 Cervical and Cervicomedullary Spinal Cord Stimulation for Chronic Pain: Efficacy and Outcomes. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Chivukula, Srinivas; Tempel, Zachary J.; Weiner, Gregory; Chen, Ching-Jen; Moossy, John Jefferson
Abstract: INTRODUCTION: The role for spinal cord stimulation (SCS) in the management of chronic spinal cord forms of pain involving cervical dermatomes or the cervicomedullary junction (CMJ) for facial pain remains largely uncharted. We reviewed outcomes with cervical and CMJ SCS performed by a single surgeon, with particular emphasis on complications and efficacy. METHODS: All patients that underwent cervical or CMJ SCS by the lead author were identified and follow-up was obtained by telephone questionnaires. Patient demographics, surgical details, outcomes and complications for all patients identified were critically reviewed. RESULTS: Of 121 patients identified that underwent at least trial SCS, 100 underwent permanent lead implantation. Indications for cervical SCS included brachial plexus lesions (8), complex regional pain syndrome (33), degenerative disc disease (4), failed neck surgery syndrome (23), chronic radiculopathy (6), and post-herpetic neuralgia (PHN) (1); for CMJ SCS, indications included trigeminal deafferentation pain (10), trigeminal neuropathic pain (4), PHN (4) and occipital neuralgia (7). Pain relief was greater along the extremities than axially, and less in the occipital area than in the head or face. Mean pain reduction averaged 56.6% at a mean follow-up of 4.2 years. Of 24 revision surgeries required, 8 were for presumed lead migration or fracture. Complications included 4 cerebrospinal fluid leaks, 5 wound infections, and 4 cases of persistent numbness or pain. Pain relief lasted an average of 3.6 years. CONCLUSION: Cervical and CMJ SCS are safe and efficacious and may provide greater relief along the upper extremities than axially, and in the head rather than in the occipital region.